Assessing Parenting Interactions With Children: Spanish Validation of PICCOLO With Fathers - Rivero, Magda; Vilaseca, Rosa; Ferrer, Fina; Guilera, Georgina (Frontiers in Psychology, 2021)
Background/Objective: To gain knowledge about mothers' and fathers' interactions with their sons and daughters, we need reliable and valid tools to assess parental behaviors that can be used for different caregivers and in a variety of cultural contexts. The aim of this study was to analyze the psychometric properties of Parenting Interactions with Children: Checklist of Observations Linked to Outcomes (PICCOLO) to assess fathers' interaction with their children at early ages. PICCOLO is an observational tool originally developed in the United States for mothers and fathers and previously validated in Spain with a sample of mothers. Methods: One hundred and ninety-one father–child dyads were observed during free-play situations at home when the children were between 10 and 47 months of age (55.0% male). The fathers auto recorded 8–10 minutes of interaction and trained evaluators assessed the recordings with PICCOLO. Results: Confirmatory factor analysis (CFA) confirmed the dimensional structure of the original version of the scale: four first-order factors (Affection, Responsiveness, Encouragement and Teaching) and one second-order factor (Parenting). The tool was found to have high inter-rater reliability at domain and total score level. Ordinal alpha and omega coefficients for each domain ranged between 0.79 and 0.85, and 0.64 and 0.79, respectively. No statistically significant differences were found in any PICCOLO domain or in the total score according to the child's gender. In assessments of the child's development with the Bayley-III scales, moderate positive correlations were found between Encouragement and receptive language (r = 0.32), and between Teaching and expressive (r = 0.34) and composite language (r = 0.31). Conclusion: The Spanish version of PICCOLO can be used to assess fathers' parenting. As PICCOLO is clearly linked to intervention goals, it is of particular interest for practitioners in early intervention and family programs.